Transforming Post-Mining Villages through Innovative BUMDes Management and Capacity Building: A Pathway to Rural Entrepreneurship and Economic Resilience in West Sumbawa - Ibrahim, Ibrahim; Mintasrihardi, Mintasrihardi; Mukhlishin, Mukhlishin; Iskandar, Syaifuddin (Faculty of Geography, Universitas Gadjah Mada, 2025)
This study explores the impact of Village-Owned Enterprises (BUMDes) on improving economic welfare and fostering entrepreneurship in the West Sumbawa gold mining area, where BUMDes have struggled to significantly enhance community welfare. The research aims to identify the innovations implemented by BUMDes to overcome these challenges. Utilizing a qualitative methodology with a case study approach, data was collected through interviews, observations, and documentation within BUMDes operating in the mining region. The analysis involved crosstab/frequency and qualitative descriptive techniques to uncover patterns and insights. The findings indicate that innovation in managing local resources is critical, encompassing the development of innovative products, the application of digital technologies, and the establishment of collaborations with external parties. These strategies have been pivotal in enabling BUMDes to address the economic needs of the community more effectively. However, the study also highlights the necessity of enhancing the managerial capacities of those running BUMDes. Without significant improvements in managerial skills, the potential of BUMDes to compete on a global scale and act as sustainable economic drivers within their communities remains limited. The research suggests that targeted capacity-building initiatives are essential for empowering BUMDes to fulfill their intended role as catalysts for rural economic growth. The study contributes to the broader understanding of how rural enterprises can innovate and adapt to changing economic landscapes, particularly in resource-rich areas, and provides practical recommendations for policymakers and stakeholders aiming to strengthen the impact of BUMDes on village economies.Received: 2024-07-09 Revised: 2024-08-08 Accepted: 2025-07-11 Published: 2025-07-31